Uso de marcadores bioquímicos para avaliar a eficiência de degradação do pesticida malathion por fotólise e processo UV/H2O2 - Imoski, Rafaela (2023)
This work aimed to evaluate the responses of biochemical markers after degradation of standard malathion and in commercial formulation by photolysis and UV/H2O2 process. The analytical method for determining the analyte was developed using high performance liquid chromatography combined with solid phase extraction. The photolysis and UV/H2O2 degradation tests were carried out in a conventional 1L photochemical reactor at times of 15, 30 and 45 minutes, with a radiation source of a 125W high-pressure mercury lamp, protected with a quartz protective bulb and immersed in the solution. The H2O2 concentration was reestablished at 100 mg L-1 every 5 minutes. Malathion concentration was monitored by HPLCDAD and the formation of by-products by GC-MS/MS. Acute toxicity was analyzed with Stegomyia aegypti larvae and phytotoxicity with Lactuca sativa seeds. To evaluate the sublethal effect of malathion and its by-products, biochemical biomarkers (AchE, GST, EST-α, EST-β, SOD and LPO) were evaluated in Stegomyia aegypti mosquitoes reared from the first stage to mosquito emergence. The chromatographic method showed adequate linearity (R2> 0.99) and recovery levels for the extraction of 76 (16.5) %. The limit of detection and quantification for malathion was 0.03 and 0.03 µg L-1, respectively. Malathion degradation showed values below the detection limit of the analytical method at all times and processes analyzed. Larvicidal activity with Stegomyia aegypti showed the greatest toxic effects for untreated samples from both processes. For phytotoxicity, a variation between inhibition, stimulation and no observed effect was observed depending on the method and time of treatment. The greatest changes in enzymatic activity were recorded for EST-β and for oxidative stress enzymes in photolysis, demonstrating the inability of the antioxidant system to eliminate the excess of radicals induced by malathion and its by-products. The treatment proved to be effective for malathion degradation, however, the formation of by-products was observed that can increase the toxicity of the treated solution, contributing to the lack of complete detoxification of the environment.